Distance Learning During the COVID-19 Pandemic: Student Perception of Aerobic Dance Practical Course - Kunjung Ashadi; M E Winarno; Oktia Woro Kasmini Handayani; Hari Setijono; Tri Rustiadi; I Nengah Sandi; Ika Jayadi (International Conference on Science, Education, and Technology, 2021)
The COVID-19 pandemic requires humans to make adjustments in various aspects of life. In education area, there are also challenges of adjustment with online learning at home. In particular, big challenges are faced by practical subjects such as aerobics dance, which require a practical online learning model. The purpose of study was to determine the perceptions of students in online learning in the aerobic dance course. To obtain these answers, a questionnaire consisting of 20 questions was distributed to all 213 students that follow the course through Google Form. The questionnaire used has met the criteria for the validity and reliability. IBM SPSS Statistics 22 is used in the process of testing the validity and reliability of the questionnaire. With the validity test using Bivariate and reliability test with the Alpha Cronbach formula. The results of respondents’ answers in Google Form were converted by Microsoft Excel 2019 program to analyze the average and percentage calculations. The data shows that students have a fairly good perception of practical learning aerobic dance based on the aspects of infrastructure, human resources, media and learning systems and also student competencies. The main problem faced by students in learning is the problem of internet signals that often occurs in online video conferencing meetings. Therefore lecturers must have a passion for work to create interesting and targeted learning innovations so that the weaknesses of online practical course learning can be minimized.